LEGAL ANALYSIS OF CONCURRENT DELAY CLAIMS IN CONSTRUCTION PROJECTS AND EVALUATION OF ENTITLEMENT USING APPORTIONMENT PRINCIPLE - JOSEPH, BINU (2015)
Concurrent delays in construction are complex and often matter of dispute in construction industry. The law is unclear in this issue and the parties generally use concurrency as an excuse to escape from their responsibility to compensate the other party. In different cases related to concurrency the judges have provided rulings based on which different principles have developed on concurrency. This indicates that there cannot be a single general principle to deal with concurrency. In this research project noted English cases related to concurrency and the rulings of the judges have been reviewed. The “Society of Construction Law (SCL)” and “Association for the Advancement of Cost Engineering International (AACEI)” have developed guidelines to deal with concurrency. A legal analysis of SCL and AACEI recommendations has been carried out with the case laws in order to arrive at best possible way to deal with a concurrency situation. As the construction projects are generally large in size and lasts for a longer period of time the delay events and the critical path of the project changes over the period of time. Therefore it is important to establish the varying dominant cause of delay and understand the relevance of each event during the span of the project duration. It is rare that two concurrent delay events overlap exactly without a dominant cause. In such an instance where a dominant cause cannot be established, it is appropriate to apply the principle of apportionment to arrive at a fair entitlement for the parties. Even though apportionment principle is generally accepted as the best recommended solution for a true concurrency it is often difficult to evaluate entitlement under apportionment. This research project by means of a case study establishes that “Window Analysis” with “Time Impact Analysis (TIA)” provides best solution to apportion the entitlements under concurrency. The results of interviews with experts on this subject have been discussed at end of this document which provides better understanding of concurrency and evaluation of entitlements and liabilities of the parties.